The supporting of Co2(OH)PO4 onto N, P Co-Doped graphene via an in-situ hydrothermal assembly synthesis for efficient oxygen reduction reaction. (18th January 2018) - Ma, Xiu-Xiu; He, Xing-Quan
Abstract: Developing efficient and durable non-noble catalysts toward oxygen reduction reaction (ORR) is an ongoing challenge. Herein, a highly efficient ORR catalyst (Co-NPG) is explored by assembling Co2 (OH)PO4 on conductive nitrogen, phosphate co-doped graphene (NPG) via an in-situ hydrothermal process. The graphene oxide matrix ammoniated by ethylenediamine not only constructs stable building blocks for hosting active sites, but also induces strong interaction between assembled cobalt-based nanoparticles. Morphology characterizations demonstrate the formation of the bulk-like structure with rough surface for the hybrid. Electrochemical measurements confirm this designed catalyst displays more efficient ORR performance than the un-ammoniated graphene oxide based one, and even comparable to that of 20 wt% Pt/C under the identical experimental conditions. The high ORR activity of the hybrid originates from the joint effects of the four aspects: first, the ammoniated graphene oxide tends to induce stronger NPs interaction than graphene oxide due to polarization, causing higher electronic conductivity and resulting in orientated growth; second, the N and P co-doping effects modulate the electronic structure of graphene, exposing more defects; third, the hybrid employs a high specific BET surface area and mesoporous characteristics, which afford quick mass transport during the ORR process; last, the synergistic coupling between the formed Co2 (OH)PO4 and NPG plays a critical role. Graphical abstract: Co2 (OH)PO4 was formed on de-protonated N, P co-doped graphene, and the designed Co-NPG hybrid exhibited excellent ORR performance. Highlights: Co2 (OH)PO4 was obtained by an in-situ hydrothermal method. The Co-NPG hybrid showed a high BET surface area of 243 m 2  g −1 . The doped N and P were of strong electronic coupling. The Co-NPG composite exhibited excellent ORR activity and stability.